Isu Hukum dan Etika dalam Praktik Anastesi di Indonesia - Adi Sakti Setionegoro; Anggraeni Endah Kusumaningrum (Prosiding Seminar Nasional Ilmu Hukum, 2024)
Anesthesia practice in Indonesia faces challenges related to the implementation of professional standards and ethics as well as legal issues that often arise. This study aims to examine the implementation of professional standards and ethics in anesthesia practice in Indonesia today and to identify legal issues that often occur and how to resolve them. This study uses a normative legal research method by analyzing primary and secondary legal materials. The results of the study indicate that although there are guidelines and codes of ethics that regulate anesthesia practice, their implementation in the field still faces obstacles such as lack of understanding of health workers, excessive workload, lack of support from hospital management, and less than optimal supervision and sanctions. Legal issues that often arise include negligence in administering anesthesia, lack of informed consent, violations of the professional code of ethics, and problems in the doctor-patient relationship. Efforts that have been made to overcome these problems include improving education and training, improving standard operating procedures, strengthening supervision and sanction mechanisms, developing non-litigation dispute resolution channels, improving communication and doctor-patient relationships, and increasing support from hospital management. However, these efforts are still not fully optimal and require further evaluation and improvement. The importance of individual awareness of each anesthesiologist to comply with professional standards and ethics and strengthening ethics education are also key factors. Close collaboration between various related parties is needed to improve the quality of anesthesia practice in Indonesia while prioritizing patient safety and welfare.